The Role of Al-Ameed Family in the Buyid Era - سليطين, نغم; سامي مرعي, (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The Buyid era is considered one of the distinguished eras in the Abbasid history. It spanned between the years 334-447 AH / 946-1055 AD. It was distinguished by a large number of brilliant literary and poetry who enriched the intellectual life with their valuable works. Families also emerged that combined the acquisition of science and political work, and from The most prominent of them is the Al-Ameed family, which was one of the most important families in which the strength of the ministry and the ingenuity of the administration met, in addition to the knowledge of philosophy. Greece and its culture, and its ideal is the book Utopia، so he strived to reach it at any cost, whether through direct political practice، education or through philosophical reflection on the events, experience and sermons of history. In ruling، he succeeded in instilling his virtues with his son Abu Al-Fath, who inherited from his father a lot of scientific and political ingenuity, and this family was an example to be